2019
DOI: 10.1590/1678-7757-2018-0480
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vivo and in vitro models to evaluate pulp temperature rise during exposure to a Polywave® LED light curing unit

Abstract: Objectives: To measure and compare in vivo and in vitro pulp temperature (PT) increase (ΔTEMP) over baseline, physiologic temperature using the same intact upper premolars exposed to the same Polywave ® LED curing light. Methodology: After local Ethics Committee approval (#255,945), local anesthesia, rubber dam isolation, small occlusal preparations/minute pulp exposure (n=15) were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…25,26 Furthermore, a recent study comparing in vitro and in vivo models to investigate temperature increase when exposed to LED LCU concluded that at clinically relevant curing times only a small difference in temperature was observed. 27 Another methodological consideration in this study was the accurate placement of the thermocouple in the pulp chamber. In part 3, we aimed to position the thermocouple close to the pulpal ceiling and the cavity floor.…”
Section: Dovepressmentioning
confidence: 99%
“…25,26 Furthermore, a recent study comparing in vitro and in vivo models to investigate temperature increase when exposed to LED LCU concluded that at clinically relevant curing times only a small difference in temperature was observed. 27 Another methodological consideration in this study was the accurate placement of the thermocouple in the pulp chamber. In part 3, we aimed to position the thermocouple close to the pulpal ceiling and the cavity floor.…”
Section: Dovepressmentioning
confidence: 99%
“…Our experimental setup can therefore be considered as a worst case clinical situation, taking additionally into consideration the small thickness of remaining dentin. A study comparing in vitro and in vivo models to investigate temperature increase when exposed to LED-LCUs concluded that at a clinical relevant CT (such as 20 s in our study) only small differences of temperature development were observed between the two models 32) . In addition, in vitro model can be considered advantageous over in vivo model for ethical reasons.…”
Section: Methodological Considerationsmentioning
confidence: 45%
“…Nevertheless, a current study evaluated how similar an in vitro model is able to reproduce temperature increase values compared to the in vivo model, in anesthetized intact, unrestored, human upper premolars, in order to validate the in vitro methodology. 27 Runnacles et al. (2019) reported that, in vitro pulpal temperature increase values were close to in vivo values when clinically relevant exposure modes were delivered.…”
Section: Discussionmentioning
confidence: 89%
“…(2019) reported that, in vitro pulpal temperature increase values were close to in vivo values when clinically relevant exposure modes were delivered. 27 Since the ethical problems in front of such in-vivo studies and the findings of Runnacles et al., in-vitro studies that evaluate the temperature increase in pulp chamber are still valid. In our knowledge, it is the first study about intrapulpal temperature increases during light-curing of compomer restorations in primary teeth and the protective effects of current pulp capping materials against these temperature increases.…”
Section: Discussionmentioning
confidence: 99%